0013 Genome-wide Association Analysis Identifies >75 Genetic Loci Associated With Sleep Duration In UK Biobank Participants. (27th April 2018) - Dashti, H S; Jones, S; Lane, J M; Wang, H; Song, Y; Patel, K; Gill, S; Gottlieb, D; Tiemeier, H; Ray, D W; Frayling, T M; Rutter, M K; et al.
Abstract: Introduction: Sleep disturbances, including short and long sleep durations, have negative consequences on health. Yet, molecular mechanisms regulating sleep and underlying the link to diseases remain poorly understood. Genome-wide association studies (GWAS) for sleep duration have thus far identified PAX8 and VRK2 signals associated with sleep duration at genome-wide significance. Methods: We performed GWAS of self-reported sleep duration ( n =446, 118) and separately for short (<7 hours/night; n =106, 192 cases) and long (>8 hours/night; n =34, 184 cases) sleep using linear/logistic regression adjusting for age, sex, 10 principal components of ancestry, and genotyping array of ~11m imputed variants in participants of European ancestry in the UK Biobank. Results: Trait heritability was 9.8% for sleep duration, 7.9% for short sleep, and 4.7% for long sleep. We identified 78, 27 and 8 independent genome-wide significant ( P <5 x 10 –8 ) loci for sleep duration, short and long sleep durations, respectively, and confirmed associations at PAX8 and VRK2 . New associations implicated genes FTO, DRD2, GNAO1, among others. Pathway analysis indicates enrichment of genes involved in brain development, long term depression and neurotransmission. A combined genetic risk score of 78 SNPs was associated with sleep duration in independent GWAS of adults [beta(se)=0.64(0.06) mins/allele; P =1.2E-25] and adolescents [beta(se)=0.15(0.07) mins/allele; P =0.03]. Strong genome-wide genetic overlap was observed between our current analysis and previous GWAS for sleep duration in adults ( r 2 =1.00; P <0.001) but not adolescents ( r 2 =0.098; P >0.05), suggesting different mechanisms regulating sleep duration across the lifespan. Mechanisms underlying short and long sleep durations were suggested to be partially distinct since there was only minor overlap among significant hits and moderate pairwise genetic correlation (Rg=-0.283, P <0.001). Genetic correlations indicated shared biological links between sleep duration and psychiatric, cognitive, anthropometric and metabolic traits (LDSC, P <1.25x10 -3 ). Conclusion: The present findings expand our understanding of the genetic architecture of sleep and the shared genetics links with disease traits. Support (If Any): This work is supported by grants NIH F32DK102323, NIH 4T32HL007901, NIH R01DK107859, NIH R35 HL135818, MGH Research Scholar Fund, the Wellcome Investigator Award, and The University of Manchester Research Infrastructure Fund.